2012
DOI: 10.1007/978-1-62703-038-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Direct and Indirect Antisperm Antibody Testing

Abstract: Antisperm antibodies (ASA) are one well-known cause of refractory infertility in both males and females. In females, a sperm immobilization test, which detects sperm-immobilizing antibodies indirectly in the patient's serum, requires complement for the reaction and thus seems to be a more specific immunological reaction. In males, an immunobead test or a mixed antiglobulin reaction test, which detects ASA directly on the sperm surface, is a screening test because of the nonspecific reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Recently, Shibahara and Koriyama reported that a sperm immobilization test, which detects sperm-immobilizing antibodies indirectly in the female patient's serum, requires complement for the reaction and thus seems to be a more specific immunological reaction. 20 On the other hand, in males, an immunobead test or a mixed antiglobulin reaction test, which detects ASA directly on the sperm surface, is an ideal screening test because of the non-specific reaction. 20 Therefore, ASA tests in sera and/or semen are useful for screening of disturbance of fertilization but not for detection of orchitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Shibahara and Koriyama reported that a sperm immobilization test, which detects sperm-immobilizing antibodies indirectly in the female patient's serum, requires complement for the reaction and thus seems to be a more specific immunological reaction. 20 On the other hand, in males, an immunobead test or a mixed antiglobulin reaction test, which detects ASA directly on the sperm surface, is an ideal screening test because of the non-specific reaction. 20 Therefore, ASA tests in sera and/or semen are useful for screening of disturbance of fertilization but not for detection of orchitis.…”
Section: Discussionmentioning
confidence: 99%
“…20 On the other hand, in males, an immunobead test or a mixed antiglobulin reaction test, which detects ASA directly on the sperm surface, is an ideal screening test because of the non-specific reaction. 20 Therefore, ASA tests in sera and/or semen are useful for screening of disturbance of fertilization but not for detection of orchitis. On the other hand, studies on testicular biopsies revealed the presence of IgG deposits in the testes from 30 to 70% of infertile male patients.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we sought to evaluate the in uence of seminal plasma ASA on the outcomes of ICSI, in a casecontrol fashion. ASA could be detected directly on sperm surface using mixed agglutination reaction (MAR) and immunobead test (IBT), which are recommended by the current WHO guidelines due to their wide availability and easy performance, or indirectly in serum or seminal plasma [22,16]. Unfortunately, no interest was given to the relevance of the targeted antigens, the targeting antibody subclass, the synergetic effect of different ASA subclasses, or the severity of autoimmunization in the current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Direct (detecting ASA on the sperm surface) and indirect (detecting ASA in the female genital tract or partners serum) testing can help identify ASA [22]. Both direct immunobead (D-IBT) and mixed antiglobulin reaction (MAR) tests show sperm bound ASA.…”
Section: Immune Disordersmentioning
confidence: 99%